2022
DOI: 10.1111/ped.15336
|View full text |Cite
|
Sign up to set email alerts
|

S/F and ROX indices in predicting failure of high‐flow nasal cannula in children

Abstract: Background A high‐flow nasal cannula (HFNC) is a useful respiratory support for children with respiratory distress; however, it elevates the risk of belated intubation. Recently, indices based on percutaneous oxygen saturation, a fraction of inspired oxygen, and respiratory rate (RR) have been suggested for the prediction of HFNC failure. We aimed to evaluate various indices predicting HFNC failure in children who started receiving HFNC at a tertiary center for 27 months. Methods Cases of HFNC failure were cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…This study aimed to evaluate the effectiveness of the ROX index in Several studies, including those by Choi S.H., 15 Kim J.H. 16 in various age groups and diagnoses, have explored the potential of the ROX index and its variations as predictors of HFNC failure in pediatric patients. However, they consistently revealed limited predictive capacity, with AUC-ROC values often in the range of 0.5 to 0.6.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study aimed to evaluate the effectiveness of the ROX index in Several studies, including those by Choi S.H., 15 Kim J.H. 16 in various age groups and diagnoses, have explored the potential of the ROX index and its variations as predictors of HFNC failure in pediatric patients. However, they consistently revealed limited predictive capacity, with AUC-ROC values often in the range of 0.5 to 0.6.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies, including those by Choi S.H., 15 Kim J.H 16 . in various age groups and diagnoses, have explored the potential of the ROX index and its variations as predictors of HFNC failure in pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the course of our study, 3 studies were published using the ROX for the pediatric population 16 , 17 , 28 . Yildizdas et al 28 and Kim et al 16 were the first authors to publish the ROX for the pediatric population; however, these studies included patients aged 0–18 years, and due to the great variability of RR in this age range, it was necessary to modulate RR with the Z score, thus changing the index value. Yildizdas et al showed that the p-ROXI (pediatric respiratory rate-oxygenation index) can be used as a good marker for predicting the risk of HFNC failure in patients with acute respiratory failure.…”
Section: Discussionmentioning
confidence: 99%
“…In the pediatric population, Yildizdas et al defined pediatric ROX to identify HFNC failure in children with different etiologies of respiratory diseases; however, they used the respiratory z score, which is relatively complicated to apply at the bedside. Subsequently, two other studies used the ROX index in the pediatric population, but only one of them was specific to infants with bronchiolitis 16 , 17 . Our hypothesis is that the ROX index is a promising predictor of the need to escalate ventilatory support from HFNC to NIV/IMV.…”
Section: Introductionmentioning
confidence: 99%